10 best teaching practices : how brain research and learning styles define teaching competencies - Tileston, Donna Walker (Thousand Oaks, Calif. ; London : Corwin, 2011)
With this book learn how to identify the needs and measure the progress of the students of the new millennium. It explores the best practices that have emerged from the 1900s and examines how they will stand up to challenges in the near future.
Previous ed.: 2005.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Effective teaching; Educational change; Learning, Psychology of